Performance assessments of the material for the traction motor cores of an electric racing kart - DEMİR, UĞUR (My University, 2021)
This paper presents the performance assessments for the traction motor of an electric racing kart, considering the different core materials. Firstly, the appropriate traction motor type is determined as a brushless direct current motor (BLDC) due to the superior features such as torque, efficiency, cooling performance and reliability. Thereafter the BLDC traction motor is optimized in Ansys RMXprt by using Taguchi\"s design of experiment (DoE) method in order to meet the vehicle requirements. The BH curves are created for steel sheet (M19_24G), amorphous (2605SA1) and soft magnetic composite (SMC) (Somaloy 1000 3P) in Ansys Maxwell Environment, which are widely used as core materials in the literature. Then, the motor models are analyzed by the finite element method in Ansys Maxwell, and the core materials that can meet the minimum requirements in terms of magnetic flux density and saturation are verified. Finally, the dynamic vehicle model is set up in Ansys Simplorer in order to evaluate the motor performances. For that purpose, a reference speed profile is created by using the measured speed from the Gothenburg carting ring, and the battery consumption characteristic and reference speed tracking performance of the motor models with different cores are evaluated in the driving cycle.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KARAKTERİZASYON VE TEST; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, CHARACTERIZATION & TESTING; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Electric racing cart; traction motor; magnetic core materials; design of experiment; driving performances; DESIGN; Electric racing cart; traction motor; magnetic core materials; design of experiment; driving performances